2020
DOI: 10.4018/978-1-7998-0058-3.ch008
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Authentic Leadership as Practical Implications of Positive Organizational Psychology

Abstract: A large body of evidence suggests that leadership can be learned, and followers may respond to such learned behavior positively. Indeed, motivation, engagement, health, and wellbeing of employees in an organisation depend on the quality of the managers to a great extent. In this context, managers need to be equipped with the skills and behaviors both to engage and to protect the health and wellbeing of their teams. In this chapter, the theoretical backgrounds of transformational leadership and authentic leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…Hence, another possible extension of this research involves investigating the multi‐dimensionality of the servant leadership style and differentiating the influence of each dimension. The fact that recent studies have found a link between satisfaction of basic psychological needs and intrinsic motivation and other types of leadership, such as authentic leadership and transformational leadership (Jensen & Bro, 2018; Valsania et al., 2016; Yavuz, 2020), both of which have some dimensions in common with servant leadership (van Dierendonck, 2011), suggests the interest and possibility of exploring the differential effects of the dimensions of servant leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, another possible extension of this research involves investigating the multi‐dimensionality of the servant leadership style and differentiating the influence of each dimension. The fact that recent studies have found a link between satisfaction of basic psychological needs and intrinsic motivation and other types of leadership, such as authentic leadership and transformational leadership (Jensen & Bro, 2018; Valsania et al., 2016; Yavuz, 2020), both of which have some dimensions in common with servant leadership (van Dierendonck, 2011), suggests the interest and possibility of exploring the differential effects of the dimensions of servant leadership.…”
Section: Discussionmentioning
confidence: 99%
“…The True North analogy has had great appeal and now seems firmly linked to leadership in the literature (Becker, 2009;Diddams & Chang, 2012;Leavy, 2016;Seco & Teixeira, 2019;Sherman, 2017). Although the characteristics of an authentic leader vary slightly from author to author, sources have a common core of principled morality, ethical judgment and actions, transparency, and self-regulation (Chan, 2005;Walumbwa, Avolio, Gardner, & Peterson, 2008;Yavuz, 2020). AL has become classified within the field of positive psychology along with ethical, servant, and spiritual leadership (Northouse, 2019), and has become popular in response to the call for higher standards of character and integrity, as it seeks to find a way to move organizations, communities, and societies forward by focusing on what is right with people, and building on those strengths (Contreras, 2016;Fry & Whittington, 2005).…”
Section: O P E R a T I O N A L I Z I N G A N I N T E R N A L C O M P mentioning
confidence: 99%
“…Because of the embeddedness of AL, it has been equated to one of the highest forms of effective leadership (Chan, Hannah, & Gardner, 2005; Eigel & Kuhnert, 2005; Yavuz, 2020), and numerous researchers have built on the view of centrality by studying the AL effect on, for instance, intrapersonal and interpersonal trust (Beddoes‐Jones, 2013; Chan et al, 2005), positive organizational behavior (Gill, Gardner, Claeys, & Vangronsvelt, 2018; Yammarino, Dionne, Schriesheim, & Dansereau, 2008), and follower performance (Guenter, Schreurs, van Emmerik, & Sun, 2017; Leroy, Palanski, & Simons, 2012; Seco & Teixeira, 2019).…”
Section: Al Definition and Development Criteriamentioning
confidence: 99%
See 2 more Smart Citations